Beauty in Chemistry Artistry in the Creation of New Molecules - Fabbrizzi, Luigi; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2012)
Margherita Venturi Enrico Marchi Vincenzo Balzani The Beauty of Chemistry in the Words of Writers and in the Hands of Scientists Luigi Fabbrizzi Living in a Cage Is a Restricted Privilege Kenneth N. Raymond Casey J. Brown Inner and Outer Beauty Carson J. Bruns J. Fraser Stoddart The Mechanical Bond: A Work of Art Jean-Pierre Sauvage David B. Amabilino The Beauty of Knots at the Molecular Level
Margherita Venturi Enrico Marchi Vincenzo Balzani The Beauty of Chemistry in the Words of Writers and in the Hands of Scientists -- Luigi Fabbrizzi Living in a Cage Is a Restricted Privilege -- Kenneth N. Raymond Casey J. Brown Inner and Outer Beauty -- Carson J. Bruns J. Fraser Stoddart The Mechanical Bond: A Work of Art -- Jean-Pierre Sauvage David B. Amabilino The Beauty of Knots at the Molecular Level.
Keywords: Chemistry; Chemistry, Organic; Chemistry, Physical organic; Polymers; Chemistry; Organic Chemistry; Polymer Sciences; Physical Chemistry